Сравнительная характеристика показателей активности воспалительного процесса при пиелонефрите на фоне пузырно-мочеточникового рефлюкса у детей раннего возраста = The comparative characteristic of indicators of activity of inflammatory process with pyelonephritis on the background of vesicoureteral reflux in children of early age - Tokarchuk, N. I.; Odarchuk, I. V. (Journal of Education, Health and Sport, 2016)
Tokarchuk N. I., Odarchuk I. V. Сравнительная характеристика показателей активности воспалительного процесса при пиелонефрите на фоне пузырно-мочеточникового рефлюкса у детей раннего возраста = The comparative characteristic of indicators of activity of inflammatory process with pyelonephritis on the background of vesicoureteral reflux in children of early age. Journal of Education, Health and Sport. 2016;6(8):734-746. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.62073 http://ojs.ukw.edu.pl/index.php/johs/article/view/3849 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 28.08.2016. УДК: 616.61-002.3:616.62-008.22-053.3 Сравнительная характеристика показателей активности воспалительного процесса при пиелонефрите на фоне пузырно-мочеточникового рефлюкса у детей раннего возраста Н. И. Токарчук, И. В. Одарчук Винницкий национальный медицинский университет им. Н. И. Пирогова, г. Винница, Украина Резюме В работе представлен анализ лабораторных показателей активности воспалительного процесса при пиелонефрите у детей раннего возраста. Определено повышение плазменной концентрации прокальцитонина и моноцитарного хемоаттрактантного протеина 1 у детей с пиелонефритом. Установлена высокая чувствительность и специфичность данных показателей при пиелонефрите у детей раннего возраста. Ключевые слова: пиелонефрит, дети раннего возраста, прокальцитонин, моноцитарный хемоаттрактантний протеин 1. The comparative characteristic of indicators of activity of inflammatory process with pyelonephritis on the background of vesicoureteral reflux in children of early age N. I. Tokarchuk, I. V. Odarchuk Vinnitsa National Pirogov Memorial Medical University, Vinnitsa, Ukraine Abstract The paper presents the analysis of laboratory indices of inflammatory process activity in case of pyelonephritis in children of early age. Determined increased plasma concentration of procalcitonin and monocyte chemoattractant protein1 inchildren with pyelonephritis. Plasma concentration of procalcitonin and monocyte chemoattractant protein 1 is higher in children with pyelonephritis on the background of vesicoureteral reflux than in children with primary pyelonephritis. It is shown that the levels of procalcitonin and monocyte chemoattractant protein 1 tended to increase with age of the examined children. The highest indicators were recorded at the age of 2 years 3 years than patients aged 1 month-1 year, 1 year-2 years and in children of the control group. Was determined increased production of markers of inflammation predominantly in girls than in boys, who were ill with pyelonephritis. This is due to the anatomical structure of the urinary system and greater probability of infection of urine and maintaining the inflammatory process in girls. Along with the increase in the degree of inflammatory activity in the kidneys increased levels of procalcitonin and monocyte chemoattractant protein 1. We have established high sensitivity and specificity of these indicators in pyelonephritis in children of early age. Key words: pyelonephritis, young children, procalcitonin, monocyte chemoattractant protein 1.